Restoratif Justice, Diversi dan Peradilan Anak Pasca Putusan Mahkamah Konstitusi Nomor 110/Puu-X/2012 - Dedy Sumardi; Mansari Mansari; Maulana Fickry Albaba (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2022)
The Constitutional Court, by Decision No. 110/Law-X/2012, repealed Articles 96, 100, and 101 of Law No. 11 of 2012 on the Child Criminal Justice System, which establishes penalties for judges, prosecutors, and investigators who do not seek discrimination against children who face the law. These provisions have no more binding legal force for judges, police, and prosecutors who do not perform their duties. The study focuses on the implementation of diversity and the impact of child protection before and after the Constitutional Court rulings. The interview data is obtained from the Banda Aceh State Court, supported by library data, and analyzed using a juridico-empirical approach. Based on the analysis of the data, it was found that the execution of diversion in the Banda Aceh State Court before the birth of the decision of the Constitutional Court Number 110/PUU-X/2012 was in accordance with the regulations of the laws in force and was accompanied by the threat of criminal offenses. After the birth of the judgment of the Constitutional Court, the execution of differences is an obligation that must be carried out by the judge but is not accompanied by the threat of a criminal offense for a judge who does not perform it. The impact of the ruling of the Constitutional Court is that there is no criminal threat to the judge, JPU, and investigator because the Constitutional Court ruling has declared Articles 96, 100, and 101 to have no binding legal force. Nevertheless, the duty of diversification remains a duty that must be enforced by law enforcement.